PENGARUH DAYA IRADIASI GELOMBANG MIKRO TERHADAP SIFAT-SIFAT FISIKA KARBON AKTIF KAYU EUCALYPTUS - Farma, Rakhmawati (Komunikasi Fisika Indonesia, 2016)
The aim of this research is to determine the influence of microwave irradiation on the physical properties of activated Carbon based Eucalyptus wood. Activated Carbon were prepared from the conventional carbonized of wood Eucalyptus for 1.5 hours and microwave assisted Potassium Hydroxide with ratio of carbon and KOH of 2:1. The samples were irradiated by using the microwave for 20 minutes and the power output of 540; 630 and 720 Watt respectively.The microwave assisted Potassium Hydroxide Carbon activation are influenced of the physical properties of the samples. The higher of output power of irradiation shows the smaller of activated Carbon.The activated Carbon were irradiated with power output of 630 Watt producing the highest percentage of Methilene Blue degradation of 96.859%, where this value is supported by the highest of Lc value of 48.4733Ã.]Â